Constraints Faced by Paddy Farmers in Palakkad District of Kerala - Parekkadan House, Sabu P J; Deepa Roy (Indian Journal of Extension Education, 2024)
The demand for rice is high in Kerala, therefore, the quality and quantity of paddy cultivation have a prominent role in Kerala. Among the various districts in Kerala, Palakkad has the highest paddy production in Kerala. However, it was observed that paddy cultivation in Palakkad district has been gradually declining over the past 20 years, both in terms of area and production. Earlier studies have shown that paddy cultivation faced various constraints. However, previous studies have rarely addressed the hurdles faced by paddy farmers in Palakkad. In this context, the present study was conducted during December 2023 to investigate and identify the constraints faced by farmers in Palakkad district in paddy cultivation. The present study used quantitative and qualitative methods to collect the data to achieve this objective. The study identified five major interlinked but distinct areas of constraints. The most important areas in which restrictions existed were; leadership and management, finance, marketing, agroecological, and inputs. Based on these findings, this study argues that paddy farmers and the Government should be receptive and responsive to the ever changing systems of paddy farming.